Simulation multi-agent de l’activité humaine : une concrétisation en ergonomie du programme de recherche technologique « cours d’action » - Yvon Haradji (Activités)
SMACH (Multi-Agent Simulation of Human Activity and Consumption in the Home) is a simulation platform that is part of EDF's research and development framework. It aims to use simulation to anticipate and reduce energy consumption at different levels of analysis (housing, neighborhood, city, country). The aim of this article is to characterize a “course-of-action” technological research program by referring to several years of SMACH research work. We mainly focus on the importance of the organic relationship between technology and human activity and we show the evolution of this organic relationship as we follow the different stages that characterize this technological research program. This article can be seen as a basis for generalizing and specifying the effective criteria for validating a technological research program and as a contribution to a reflection on design in ergonomics.